Gene Amplification, ABC Transporters and Cytochrome P450s: Unraveling the Molecular Basis of Pyrethroid Resistance in the Dengue Vector, Aedes aegypti - Bariami, Vassiliki; Jones, Christopher M.; Poupardin, Rodolphe; Vontas, John; Ranson, Hilary (PLOS Neglected Tropical Diseases, 2012)
Author Summary Dengue is the most rapidly spreading arboviral infection of humans and each year there are 50–100 million cases of dengue fever. There is no vaccine or drug to prevent dengue infection so control of the mosquitoes that transmit this virus is the only option to reduce transmission. Removing mosquito habitats close to human homes can be effective but in reality most dengue control programmes rely on a small number of chemical insecticides. Therefore, when the mosquito vectors develop resistance to the available insecticides, dengue control is jeopardized. In this study we examined the causes of resistance to the insecticide class most commonly used in mosquito control, the pyrethroids. We found that a group of genes, which have been implicated in detoxifying these insecticides in other populations of dengue vectors, were highly over expressed in both these Caribbean populations and we investigated the molecular basis of this increased expression. The next steps, which will be a considerable challenge, are to utilize this information to develop effective means of restoring insecticide susceptibility in dengue vectors.